1984
DOI: 10.2135/cropsci1984.0011183x002400030023x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Genetic Male Sterile Mutants in a Semidwarf Japonica Rice Cultivar1

Abstract: Genetic male sterility was induced in the semidwarfjaponica rice (Oryza sativa L.) cultivar M‐101 by treatment of seeds with 30 kR of gamma rays. In the X2 generation, 251 partially sterile plants which presumably were true steriles that were setting seed due to outcrossing, were selected and designated as Group I lines. Fertile progenies of these X2 plants were considered to beputative Fl's from natural crosses. By a series of progeny tests, which eventually involved confirmed crosses, eight lines which carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

1987
1987
2005
2005

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Data collected from the segregating populations at Davis in 1987 also confirmed that the sterility in each of the seven previously reported mutants (MESE et al 1984), Gl to G7 in the present study, was controlled by a single recessive gene (Table 3).…”
Section: Progeny Testssupporting
confidence: 88%
See 4 more Smart Citations
“…Data collected from the segregating populations at Davis in 1987 also confirmed that the sterility in each of the seven previously reported mutants (MESE et al 1984), Gl to G7 in the present study, was controlled by a single recessive gene (Table 3).…”
Section: Progeny Testssupporting
confidence: 88%
“…Lack of desirable ms mutants was one of the major reasons for carrying out this project in rice. MESE et al (1984) reported that 1-2, one of the 11 gamma ray induced ms mutants would be useful for its high outcrossing rate. Their results was confirmed by the present study: 1-2, coded as Gl in this study, was identified as one of the best in terms of stableness and completeness of the male sterility and the outcrossing rate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations